Does plural dominance play a role in spoken picture naming? A comparison of unimpaired and impaired speakers - Biedermann, Britta-Andrea; Beyersmann, E.; Mason, C.; Nickels, L. (2013)
This study investigates the effect of frequency on plural processing. In particular it explores the effect of relative frequency differences between plurals and their singular forms on the representation of plurals. This paper reports data from a group of thirty-eight unimpaired speakers and compares their spoken picture naming of single and multiple objects to that of two people with acquired language impairments (aphasia). For both participant groups (unimpaired and impaired), we observed two key findings for picture naming: first, plurals that are lower in frequency than their singulars (singular-dominant plurals) are responded to more slowly or with more errors compared to their singulars. Second, for plurals that are higher in frequency than their singulars (plural-dominant plurals), no difference in reaction time or error rate was detected between singulars and plurals. By capitalising on patterns observed in both unimpaired and impaired language processing, this study suggests that plural-dominant plurals are stored differently from singular-dominant plurals. © 2013 Elsevier Ltd.